Correlation and Association of Serum B12 Levels in Type-2 Diabetes Mellitus Patients Treated with Metformin: A Study Conducted at a Tertiary Care Hospital of Gujarat (GAIMS Journal of Medical Sciences, 2024)
Background: Type 2 Diabetes mellitus(T2DM) is the most common endocrine disorder, affecting millions of people, leading to morbidity and mortality. Metformin is most widely used antidiabetic drug due to various reasons. Long-term metformin treatment in type 2 diabetes mellitus patients can cause vitamin B12 insufficiency. Severe deficits, if untreated, may lead to life-threatening neurological issues, which are often overlooked and undertreated.Objective: To analyze the correlation between the duration and dosage of metformin treatment of more than one year in T2DM Patient and their combined impact on serum B12 levels among T2DM patients.Materials and Methods: Hospital-based Cross-Sectional observational study evaluated 42 diabetic subjects, encompassing both sexes aged 18 to 70 years, who had been on metformin medication for more than one year. Assessment involved a comprehensive questionnaire and measurements of FBS, HbA1c, and serum B12 levels. Additionally, data on Metformin Dosage and Duration of its use were collected. B12 deficiency was defined as serum B12 levels ≤ 200 pg/ml. Data analysis was conducted by statistically comparing the mean vitamin B12 levels in each group using the One-Way ANOVA test through SPSS version 23 software.Results: Increase in the duration of metformin drug usage correlates with a significant decrease in serum vitamin B12 levels, as confirmed by ANOVA test results (p < 0.05).Conclusions: This study finding indicate that vitamin B12 deficiency is linked to a higher risk of worsening diabetic neuropathy. Therefore, individuals with diabetes who take higher doses of metformin (over 1000mg) for extended periods (≥ 8 years) should undergo regular monitoring of their vitamin B12 levels. Proactive use of vitamin B12 supplementation, whether for prevention or treatment, can help mitigate this concern.